A wireless body sensor network based on dynamic power control and opportunistic packet scheduling mechanisms - Fernandes, Duarte Manuel Azevedo (2015)
The usage and deployment of Wireless Body Sensor Networks (WBSN) as a part of Cyber-Physical Systems (CPS) are rapidly increasing in many different real-time monitoring and applications. This emergent network has strong Quality of Service (QoS) requirements and, as it is a recent field of research, it is not yet clear if these requirements can be guaranteed in severe fading and external RF interference conditions, particularly the reliable communication needed for critical applications. This is the scope of the PROTACTICAL project, which the main goal is to ensure the QoS requirements in critical applications (First Responder) through exploitation of fading characteristics of on-body channel and external interference RF of coexistent systems and devices in real scenarios. The resulting mechanisms of this work will operate between MAC and Network layer and will be implemented using Hardware/Software co-design (FPGA) in order to evaluate all trade-offs.